Container-Based Serverless Computing with AI-Driven Resource Optimization for Cloud Fault Tolerance - Mongia, Vikas (International Journal of Computer Sciences and Engineering, 2023)
The exponential growth of cloud computing services has led to increased concerns regarding fault tolerance, energy efficiency, and resource optimization. This paper introduces a novel approach combining container-based serverless architecture with artificial intelligence for dynamic resource management and fault prediction. Our system employs deep learning algorithms for workload prediction, reinforcement learning for resource allocation, and ensemble methods for failure detection. To forecast workloads, we utilized historical and real-time data with sequence modeling techniques, achieving accurate demand predictions. Failure detection leveraged ensemble methods, combining diverse predictive algorithms to enhance robustness. Experimental results from a three-month deployment demonstrate significant improvements: an 85% reduction in energy consumption, a 40% decrease in response latency, and a 60% lower operational cost while maintaining 99.99% service availability. These improvements stem from the system`s AI-driven predictive workload management, efficient resource allocation strategies, and robust failure detection mechanisms. These results surpass current industry standards and existing academic solutions by leveraging the synergy between containerization, serverless computing, and AI-driven optimization.